Rational design of oxygen deficient TiO2−x nanoparticles conjugated with chlorin e6 (Ce6) for photoacoustic imaging-guided photothermal/photodynamic dual therapy of cancer. Issue 3 (2nd January 2020) - Jiao, Xiaodan; Zhang, Wei; Zhang, Lei; Cao, Yang; Xu, Zhigang; Kang, Yuejun; Xue, Peng
Abstract : Surface activation of TiO2− x NPs by APTES and subsequent Ce6 conjugation enabled highly efficient PA imaging-guided PTT/PDT. Abstract : Oxygen deficient TiO2− x nanoparticles (NPs) have been recognized as a category of new-fashioned photothermal agents to offer safer PTT. However, the surface of TiO2− x NPs is deficient in free active groups or radicals to conjugate functional therapeutic molecules, which seriously impedes their in-depth development for versatile medical applications. In this study, surface activation of TiO2− x NPs was realized by the facile conjugation of (3-aminopropyl)triethoxysilane (APTES) through the formation of a stable Si–O–Ti bond, and photosensitizer chlorin e6 (Ce6) was successfully modified onto the TiO2− x NP surface and with a considerably high loading content. The resultant TiO2− x @APTES/Ce6 (TAC) NPs displayed decent biosafety, rapid tumor enrichment and outstanding performance in photoacoustic (PA) imaging. Taking advantage of the intense photo-absorption in the near-infrared (NIR) region and high dose of conjugated Ce6, a powerful antitumor effect was realized based on the combination of hyperthermia-induced cell ablation and cytotoxic reactive oxygen species (ROS)-triggered apoptosis both in vitro and in vivo . Moreover, PA imaging guidance was exceptionally useful for locating the tumor position and optimizing the treatment regimens. Apart from Ce6, this elaborate modification strategy for TiO2− x is believed to be universal for steadily binding more versatile therapeutic agents, which would definitely favor the development of multifunctional TiO2− x -based nanocomplexes for enhanced tumor treatment.